Evaluation of the Electrically-Evoked Stapedial Reflex Threshold in Pediatric Cochlear Implant Users with High-Frequency Probe Tones - Palani, Saravanan; Alexander, Arun; Sreenivasan, Anuprasad (International Archives of Otorhinolaryngology, 2022)
Introduction Measurement of the electrically-evoked stapedial reflex threshold (ESRT) is an objective tool used to set the comfort levels in pediatric cochlear implant (PCI) users. The levels of ESRT have a strong correlation with comfort levels. However, the clinical utility of ESRT is limited because the ESRT response is not observed in all cochlear implant users.Objective To assess the effects of probe-tone frequency on ESRT and its relationship with the behavioral comfort levels in PCI users.Methods A total of 14 PCI users aged between 5 and 8 years participated in the study. The ESRT levels were measured using high-frequency probe tones (678 Hz and 1,000 Hz), and the default 226 Hz probe tone. The ESRT was measured with single-electrode stimulation across the three electrode locations (basal [E01]; middle [E11]; and apical [E22]). The ESRT levels measured with different probe tone frequencies were compared with the behavioral comfort levels.Results The mean ESRT levels using 1,000Hz and 678 Hz were lower than those measured using 226 Hz, but there was no main effect of probe-tone frequency (p > 0.05). A significantly high incidence of successful ESRT measurements occurred with higher-frequency probe tone (p < 0.039). Additionally, ESRT using higher probe tones significantly correlated with comfort levels.Conclusion The ESRT with higher probe tones was correlated with behavioral comfort levels and increased the success rate of the measurements. Higher-frequency probe tones may be useful whenever ESRT with 226 Hz is not measurable.
Keywords: cochlear implant; electrical stapedius reflex threshold; comfort levels; probe tone